2011
DOI: 10.4103/0300-1652.93801
|View full text |Cite
|
Sign up to set email alerts
|

Elective caesarean section in a tertiary hospital in Sokoto, north western Nigeria

Abstract: Background:Elective caesarean sections have been considered safer for both mother and the fetus compared to their emergency counterpart. However, emergency caesarean sections have continued to form bulk of caesarean deliveries in our facility.Objective:The objective of this study was to determine the caesarean section rate together with the trend, indications, and maternal mortality associated with elective caesarean operation.Materials and Methods:A retrospective analysis of clinical records of all the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 8 publications
5
21
5
Order By: Relevance
“…Rates of 16.9% and 18% reported in studies done in southwest, Nigeria were similar to that of the present study. 24,25 Emergency caesarean section rate of 90.4% reported in the present study is higher than those reported by Aisien 20 , Okonofua 26 and Nwobodo 27 but lower than 97.4% reported by Buowari. 29 The implication is that perinatal mortality rate may continue to rise until caesarean section is done as elective rather than emergency procedure.…”
Section: Discussioncontrasting
confidence: 56%
“…Rates of 16.9% and 18% reported in studies done in southwest, Nigeria were similar to that of the present study. 24,25 Emergency caesarean section rate of 90.4% reported in the present study is higher than those reported by Aisien 20 , Okonofua 26 and Nwobodo 27 but lower than 97.4% reported by Buowari. 29 The implication is that perinatal mortality rate may continue to rise until caesarean section is done as elective rather than emergency procedure.…”
Section: Discussioncontrasting
confidence: 56%
“…The increase in caesarean section rates is largely driven by several factors which include societal demands for improved foetal outcome, protection of pelvic floor, and the aspiration of obstetricians to meet these demand [10].…”
Section: Introductionmentioning
confidence: 99%
“…Elective surgery has been judged to be better than emergency surgery [10,11], moreso the operation avails the patient the benefit of a team of an anaesthetist, neonatologist, obstetrician and the operating theatre staff [2]. Anaesthetic complications are more likely to occur in patients who need emergency caesarean section, and are administered general anaesthesia sooner than 4-6 hours after taking food and fluids [12].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends that the Caesarean section rate should be 10-15% 7 . However, there is wide variation of this rate globally as well as locally 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Although elective Caesarean section is considered safer for both mother and fetus, when compared with emergency Caesarean section, the latter continued to exact its dominance in frequency in most health facilities in Nigeria 8,9 . Regional anaesthesia is generally recommended over general anaesthesia in term of safety for both the parturient and the fetus 10,11 .…”
Section: Introductionmentioning
confidence: 99%